Osage, the People from the Stars; Origin Story (Symphony in the Flint Hills, 2019)
Introduction: Wah-kon-da, the mystery force of the universe, sent the Osage down from the sky to be the caretakers of Earth, which they called the Sacred One. They were the children of Grandfather Sun and, at that time, they were called the Little Ones. Courtesy of the Osage National Museum.